2021
DOI: 10.1111/vox.13209
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil antigen 2 sequence‐based typing: Joining the hunt for the CD177 answer

Abstract: Background and Objectives: Isoantibodies to human neutrophil antigen 2 (CD177) have been associated with several clinical conditions but to date the molecular basis for altered or non-expression has not been determined. Reliance on phenotyping and crossmatch to investigate these neutropenic clinical cases are inconvenient for the patients and demanding of resources within the laboratory. Therefore, a molecular approach has been introduced to address both issues. Materials and Methods:A DNA panel of 100 randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The SNP c.787A > T is a nonsense SNP that terminates the protein translation and causes the HNA‐2 expression defect. Our previous study revealed that c.787T homozygosity is the primary genetic determinant for HNA‐2 deficiency, 16 which was confirmed by independent studies from other groups 17,18,23,24 …”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The SNP c.787A > T is a nonsense SNP that terminates the protein translation and causes the HNA‐2 expression defect. Our previous study revealed that c.787T homozygosity is the primary genetic determinant for HNA‐2 deficiency, 16 which was confirmed by independent studies from other groups 17,18,23,24 …”
Section: Discussionmentioning
confidence: 53%
“…Our newly developed genetic assays will enable the reliable prediction of risks for HNA‐2‐related diseases in humans and will facilitate the diagnosis and prognosis of HNA‐2‐associated human disorders. Most importantly, our assays will significantly reduce the requirement for labour‐intensive laboratory tests and the associated inconvenience of patients 18 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations